Sustainable Consumption from a Domestic Food Purchasing Perspective Among Hungarian Generation Z - Garai Fodor, Mónika; Vasa, Laszlo; Popovics, Anett (Decision Making: Applications in Management and Engineering, 2024)
The relevance of the study is the global consumer trend towards sustainability. Sustainable consumption has positive environmental, social, and economic impacts, which makes it a key issue in the context of food consumption. Preference for regional, and domestic products can significantly support sustainable consumption. The study focused on the demographically and economically important Generation Z from the perspective of sustainable consumption. The main research objective of the study is to analyze the Hungarian food purchasing habits of Generation Z and to segment Generation Z according to the Hungarian food consumption criteria to characterize potential target groups. During the research, qualitative and quantitative data collection was carried out. The study focuses on the presentation of the results of the latter. In the quantitative survey, we conducted a pre-tested standardized questionnaire online survey. Subject recruitment was carried out using a snowball sampling method, resulting in 518 evaluable questionnaires. In a quantitative study, distinct segments of Hungarian food consumers were characterized according to their food consumption preferences. The research also demonstrated that the groups of Generation Z according to Hungarian food consumption preferences differ significantly from each other in terms of their perception of Hungarian food. The research concludes that Generation Z is a group of domestic food consumers with specific characteristics, who could be the main base for sustainable consumption. For those who have not yet developed this motivation, the main reasons are an unsophisticated preference system and a lack of education. Systematic marketing activities aimed at the first component of attitudes are therefore most needed to attract these segments.